ANALISA DATA MINING DENGAN MENGGUNAKAN TRANSAKSI PENJUALAN UNTUK MENGETAHUI POLA BELI KONSUMEN PADA MINI MARKET MGM KENDARI MENGGUNAKAN METODE APRIORI BERBASIS WEB - Nelisa, Nelisa; Khairunnisa, Khairunnisa (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze consumer purchasing patterns at Mini Market MGM Kendari using data mining techniques with a web-based Apriori algorithm. The data used in this research consists of sales transactions collected over a specific period and analyzed to identify product associations frequently purchased together. Through the data preprocessing process and the application of the Apriori algorithm, several association rules with significant support and confidence values were identified. The analysis results indicate strong correlations between certain products, which can be utilized by store management to optimize marketing strategies, inventory management, and product layout within the store. The implementation of research findings in a web-based system enables real-time monitoring and analysis of purchasing patterns, allowing business decisions to be made based on more accurate data. Thus, this study contributes to enhancing the operational efficiency and profitability of Mini Market MGM Kendari by utilizing data mining technology in retail business management.